Usage Ethics in Medical Education in Islamic Countries - Mousavi, Seyyed Reza (مجله اخلاق پزشکی - علمی پژوهشی, 2016)
The Medical education exists to maintain and regulate the standards of medical practice, protect the interests of the patients, supervise medical students, and give guidelines on ethical issues. The educational Ethics provide general guidelines, and any disciplinary designated and will judge each case on its merits. This is not a comprehensive document and interpretation will depend upon circumstances. Medical students will be given opportunity to justify their actions to apply ethics.